2019
DOI: 10.1111/manc.12293
|View full text |Cite
|
Sign up to set email alerts
|

A Trendy Approach to UK Inflation Dynamics1

Abstract: This paper uses a 'trendy' approach to understand UK inflation dynamics. It focuses on the time series to isolate a low-frequency and slow-moving component of inflation (the trend) from deviations around this trend. We find that this slow-moving trend explains a substantial share of UK inflation dynamics. International prices are significantly correlated with the short-term cyclical movements in inflation around its trend, and the exchange rate is significantly correlated with movements in the slow-moving, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Even though our inflation data seems to be stationary for the samples under scrutiny in this paper, this variable is known for its strong persistence. For this reason, Cogley and Sbordone (2008) have suggested to introduce trend inflation among the explanatory variables in the NKPC equation (see also Stock and Watson (2007); Nason and Smith (2016); Cecchetti et al (2017); Eusepi and Preston (2018); Forbes et al (2019)). Although very appealing, this extension has the drawback that this extra right hand side variable is not observable, and as such, it is not so convenient to implement.…”
Section: Discussionmentioning
confidence: 99%
“…Even though our inflation data seems to be stationary for the samples under scrutiny in this paper, this variable is known for its strong persistence. For this reason, Cogley and Sbordone (2008) have suggested to introduce trend inflation among the explanatory variables in the NKPC equation (see also Stock and Watson (2007); Nason and Smith (2016); Cecchetti et al (2017); Eusepi and Preston (2018); Forbes et al (2019)). Although very appealing, this extension has the drawback that this extra right hand side variable is not observable, and as such, it is not so convenient to implement.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of long‐term patterns of inflation was developed by Forbes et al., who found that a ‘trendy’ (p. 23) rather than more prescriptive approach was beneficial to understanding the complex factors which have shaped the value of sterling over time. They concluded that given the nature of Britain's comparatively open economy and dependency on imports and monetary flows, international prices and exchange rates have been the dominant factor that explain Britain's inflation dynamics in recent decades.…”
mentioning
confidence: 99%